2013
DOI: 10.1073/pnas.1302257110
|View full text |Cite
|
Sign up to set email alerts
|

CCT chaperonin complex is required for efficient delivery of anthrax toxin into the cytosol of host cells

Abstract: Bacterial toxins have evolved successful strategies for coopting host proteins to access the cytosol of host cells. Anthrax lethal factor (LF) enters the cytosol through pores in the endosomal membrane formed by anthrax protective antigen. Although in vitro models using planar lipid bilayers have shown that translocation can occur in the absence of cellular factors, recent studies using intact endosomes indicate that host factors are required for translocation in the cellular environment. In this study, we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…LF can be artificially introduced into the cytosol, bypassing the endocytic pathway by briefly pulsing LT-pretreated cells with acidic pH (Slater et al, 2013). We added the vacuolar ATPase inhibitor Bafilomycin A during LT pre-treatment to ensure that none of the toxin complexes enter through endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…LF can be artificially introduced into the cytosol, bypassing the endocytic pathway by briefly pulsing LT-pretreated cells with acidic pH (Slater et al, 2013). We added the vacuolar ATPase inhibitor Bafilomycin A during LT pre-treatment to ensure that none of the toxin complexes enter through endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…, ; Kashuba, Pokrovskaja, Klein, & Szekely, ; Lingappa et al . , ), and the human TRiC is also involved in translocation of the anthrax toxin into host cells (Slater, Hett, Clatworthy, Mark, & Hung, ). Although it is difficult to modulate TRiC expression in RBCs, the recent advances in using hematopoietic stem cell based screening to study malaria (Egan et al .…”
Section: Discussionmentioning
confidence: 99%
“…The human TRiC machinery is co-opted by other microbes. TRiC subunits are recruited by viral proteins where they may play a role in viral replication (Hong et al, 2001;Inoue et al, 2011;Kashuba, Pokrovskaja, Klein, & Szekely, 1999;Lingappa et al, 1994), and the human TRiC is also involved in translocation of the anthrax toxin into host cells (Slater, Hett, Clatworthy, Mark, & Hung, 2013). Although it is difficult to modulate TRiC expression in RBCs, the recent advances in using hematopoietic stem cell based screening to study malaria (Egan et al, 2015) may prove useful in clarifying the role of RBC TRiC in malaria protein export.…”
Section: Discussionmentioning
confidence: 99%
“…The chaperonin inhibitor HSF1A has no effect on the protease activity of TcdB in vitro; however, we cannot exclude the possibility that TRiC/CCT5 plays a role in the refolding of the autoprotease domain of the clostridial glucosylating toxins. It was recently reported that TRiC/CCT is involved in the action of anthrax toxin (56). These studies focused on the lethal toxin (LFN) of the tripartite anthrax toxin, which is a zinc-dependent metalloprotease.…”
Section: Discussionmentioning
confidence: 99%